Post-pandemic scenarios. The role of the Italian National Recovery and Resilience Plan (NRRP) in reducing the gap between the Italian Central-Northern regions and Southern ones - Stefania Palmentieri (AIMS Geosciences, 2023)
The Covid-19 pandemic and the Ukraine crises fit into the difficult Italian context, which have already been marked by a deep socioeconomic gap between the Centre-North and the South of the country. After a brief examination of the causes that have led to this gap, starting from the analysis of geographical studies on the subject and elaborations of data provided by important research centres in the field, this study aims to point out the sectors of Southern Italy present greater criticalness and backwardness compared to the rest of the country. Then, we identify the most suitable programmatic lines to increase investments in such sectors, as already provided for the Italian National Recovery and Resilience Plan (NRRP—in Italy PNRR), a program with which the government intends to manage Next Generation EU funds or NGEU (the economic recovery and revitalization tool introduced by the European Union to restore the losses caused by the pandemic). The article concludes with a reflection on the main reasons for the difficulties that the NRRP is encountering by implementing this program, mainly related to the insufficient allocation of resources and competencies of the territorial authorities that are entrusted with the task of managing and planning policies to rebalance the country*s growth potential.